Efektivitas E-modul Instalasi Penerangan Listrik di SMK Negeri 1 Sutera - Rizky Saputra; Usmeldi Usmeldi (Dinasti Research, 2021)
This study aims to determine the effectiveness of the e-module for electric lighting installations at SMK Negeri 1 Sutera. This research was conducted using a type of experimental research which was categorized into the type of pre-experimental design with the One Group Pretest Posttest Design. The data obtained were analyzed using Effect Size and classical completeness analysis. Attitude assessment using a questionnaire with percentage analysis technical. Based on the research results, it was obtained that the average pretest before using the e-module learning media was 58.1 and the posttest average value was 72.6. From the calculation results, the Effect Size analysis value is 1.069 with the categorization of taste on a large scale. While the attitude assessment obtained an average result of 91.25 for a standard deviation of 12.26.